The burden of cough in idiopathic pulmonary fibrosis and other interstitial lung diseases: a systematic evidence synthesis - Rhiannon Green; Michael Baldwin; Nick Pooley; Kate Misso; Maureen PMH Rutten-van Mölken; Nina Patel; Marlies S. Wijsenbeek (Respiratory Research)
Abstract Background Cough remains a persistent symptom in patients with idiopathic pulmonary fibrosis (IPF) and other interstitial lung diseases (ILDs). To inform future research, treatment and care models, we conducted the first systematic synthesis of evidence on its associated burden. Methods A literature search was performed for articles published between January 2010 and October 2023 using databases including Embase, MEDLINE and the Cochrane Library. Studies in patients with IPF and other ILDs reporting cough-related measures were eligible for inclusion. Included studies were categorised based on the types of ILD they examined and their design. Study details, patient characteristics and outcomes were extracted, and the risk of bias was assessed. A narrative synthesis approach was employed to interpret the findings. Results Sixty-one studies were included: 33 in IPF, 18 in mixed-ILDs, six in connective tissue disease-associated-ILDs and four in sarcoidosis. Across the studies, a range of tools to assess cough and its impact were used. The most frequently used measures of cough were cough severity visual analogue scale (VAS) and objective cough counts, whereas the most frequently used health-related quality of life (HRQoL)/impact measures were the St. George’s Respiratory Questionnaire (SGRQ) and Leicester Cough Questionnaire (LCQ). In IPF, studies consistently reported correlations between various cough and HRQoL measures, including between cough VAS scores and objective cough counts, LCQ scores and SGRQ scores. Similar correlations were observed in studies in other ILDs, but data were more limited. Qualitative studies in both IPF and other ILDs consistently highlighted the significant cough-related burden experienced by patients, including disruption of daily activities, fatigue and social embarrassment. Although there were no studies specifically investigating the economic burden of cough, one study in patients with fibrotic ILD found cough severity was associated with workplace productivity loss. Conclusions Our study underscores the heterogeneity in assessing cough and its impact in IPF and other ILDs. The findings confirm the negative impact of cough on HRQoL in IPF and suggest a comparable impact in other ILDs. Our synthesis highlights the need for standardised assessment tools, along with dedicated studies, particularly in non-IPF ILDs and on the economic burden of cough.